Relação da proporção ômega 6/3 na dieta da gestante com a variação transgeracional do perfil metabólico e incorporação de ácidos graxos no tecido hepático - Halfen, Simone (2012)
The essential fatty acids alpha-linolenic acid (α-LNA 18:3 n-3) and linoleic acid (LA 18:2 n-6) fatty acids are precursors of polyunsaturated very long chain (PUFA-VLC) families omega-3 and omega-6. These fatty acids when consumed during pregnancy are important for brain development and adaptation of the retina and fetal tissues, influencing the metabolic pathways of fatty acids in the offspring. Based on this, we seek to verify the relationship of the influence of the ratio of omega 6/3 in the diet of pregnants with the metabolic profile of fatty acids and liver tissue in subsequent generations. For this we used 48 rats (Rattus norvegicus) Wistar, 36 females and 18 males for the founder generation (G0) with the control group (CONT) received a diet with fat source as soybean oil and omega group (OM) received the diet with linseed oil. From these groups, the animals were selected for the training of two generations (F1 and F2). The animals receiving the CONT followed the control diet while the OM group was divided into two new groups, one receiving control diet (OM/CONT) and the other keeping the feed omega (OM/OM). The incorporation of fatty acids (FA) of omega-3 was higher in liver of rats in the group OM, while the FA of omega-6 had a greater uptake of the liver tissue of the CONT group. A major change can be observed in the amount of oleic AG in liver tissue, since the merger occurred higher in the group CONT and the lowest in OM/CONT, demonstrating that the diet provided to the G0 may have somehow influenced the incorporation of generations F1 and F2. This remodeling enzyme was also sufficient to change the outcome of NEFA, which demonstrated decreased lower lipid mobilization in the same group.